Implementation of Montessori-Based Kasindra Media in Developing Five Sensory Literacy of Children Aged 4-5 Years - Fadilla Zahwa Ismaputri; Ida Yeni Rahmawati; Muhammad Azam Mutaqqin (IKIP PGRI Bojonegoro, 2026)
This study aims to analyze the implementation of Kasindra media (five senses box) and its contribution to the development of sensory literacy in children aged 4–5 years at Dharma Wanita Wagirkidul Kindergarten. The study used a qualitative descriptive design to examine the learning process, multisensory play activities, and children's responses during media use. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that Kasindra was implemented systematically through structured, multisensory play activities that engaged children's five senses. This media contributed to children's ability to recognize, differentiate, and verbally express sensory stimuli. In addition to these main impacts, Kasindra also supported improvements in children's social interactions, communication skills, and self-confidence. The value of Kasindra's innovation lies in integrating sensory stimulation into contextually and play-based learning. This study was limited to one PAUD unit, so further research with a broader scope and duration is needed.